GENDER DIFFERENCES AND THE USE OF METADISCOURSE MARKERS IN WRITING ESSAYS - Pasaribu, Truly Almendo (Sanata Dharma University, 2017)
AbstractThis study aims at investigating metadiscourse markers in academic essays written by male and female students. With the goal in mind, 20 essays written by EFL female students and 20 essays written by EFL male students were chosen. These data were analyzed based on the metadiscourse framework proposed by Hyland (2005). The findings revealed that both male and female writers employed more interactive markers than interactional markers due to the fact that both genders inserted transition markers frequently to guide readers through the texts. However, a cultural factor may influence the writersâ€™ tendency not to use transition markers showing arguments. Furthermore, although male students employed more interactional markers, female students used more markers in interactional sub-categories except self-mentions. Although it is assumed that women prefer to use a more personalized style, male writers in this study also personalized their essays by using self-mentions. One possible reason was that the use of these features tended to be more field-specific than gender-specific. The findings and discussion indicated that gender is not the only factor influencing the use of metadiscourse markers. Other possible variables discussed in this study should be taken into account.DOI: https://doi.org/10.24071/ijhs.2017.010110Â